2014
DOI: 10.1186/1477-7819-12-151
|View full text |Cite
|
Sign up to set email alerts
|

Expression of fibroblast specific protein-1 in pleural tuberculosis and its clinical biological significance

Abstract: BackgroundFibroblast specific protein-1 (S100A4) is related with many fibrotic diseases, but its role in the pathogenesis of pleural fibrosis has not been fully elucidated. Then we aim to investigate the expression and effect of fibroblast specific protein-1 (S100A4) in pleural tuberculosis and, subsequently, pleural fibrosis.MethodsThe expression of S100A4 in pleura was examined in 30 patients with pleural tuberculosis and 5 control (disease-free) patients by immunohistochemistry using the streptavidin-peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…S100A4 played important role in organ fibrosis. In our previous study, we have reported that S100A4 is highly expressed in pleural tuberculosis 10. Xie R et al 17 found S100A4 mediated endometrial cancer invasion and was a target of TGF-β signaling.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…S100A4 played important role in organ fibrosis. In our previous study, we have reported that S100A4 is highly expressed in pleural tuberculosis 10. Xie R et al 17 found S100A4 mediated endometrial cancer invasion and was a target of TGF-β signaling.…”
Section: Discussionmentioning
confidence: 90%
“…In our previous study, we have reported that S100A4 is highly expressed in pleural tuberculosis. 10 Xie R et al 17 found S100A4 mediated endometrial cancer invasion and was a target of TGF-β signaling. Matsuura et al 18 reported functional interaction between Smad3 and S100A4 became important regulator for TGF-β-mediated cancer cell invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Это, с одной стороны, способствует продолжаю щемуся повреждению и хроническому персистирую щему воспалению, а с другой -вызывает чрезмерное накопление компонентов ЕСМ и избыточный син тез коллагена миофибробластами; в результате этого нормальная ткань легкого замещается постоянной рубцовой тканью [38]. Специфический протеин 1 фибробластов (S100A4) играет важную роль в фено типической трансформации мезотелиальных клеток плевры и развитии фиброза плевры при туберкулез ном плеврите [42].…”
Section: резюмеunclassified